2017
DOI: 10.1371/journal.pgen.1006931
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hyper-editing underlies temperature adaptation in Drosophila

Abstract: In Drosophila, A-to-I editing is prevalent in the brain, and mutations in the editing enzyme ADAR correlate with specific behavioral defects. Here we demonstrate a role for ADAR in behavioral temperature adaptation in Drosophila. Although there is a higher level of editing at lower temperatures, at 29°C more sites are edited. These sites are less evolutionarily conserved, more disperse, less likely to be involved in secondary structures, and more likely to be located in exons. Interestingly, hypomorph mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 56 publications
6
65
0
Order By: Relevance
“…It's reasonable that RNA editing may play roles in response to environmental stress through changing the corresponding gene functions. Our results also indicated that RNA editing was more prevalent at lower temperatures, which is also accord with a previous study in animal, that the phenotypic consequences of ADAR (RNA editing factors in animal) deficiency in Drosophila melanogaster indicated that RNA editing plays an integral role in temperature adaptation by sensing and acting globally on RNA secondary structure (Buchumenski et al 2017). It is possible that differential RNA editing is one process that allows poikilothermic animals and higher plants, such as fly and grape, to rapidly adapt to varying environmental temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…It's reasonable that RNA editing may play roles in response to environmental stress through changing the corresponding gene functions. Our results also indicated that RNA editing was more prevalent at lower temperatures, which is also accord with a previous study in animal, that the phenotypic consequences of ADAR (RNA editing factors in animal) deficiency in Drosophila melanogaster indicated that RNA editing plays an integral role in temperature adaptation by sensing and acting globally on RNA secondary structure (Buchumenski et al 2017). It is possible that differential RNA editing is one process that allows poikilothermic animals and higher plants, such as fly and grape, to rapidly adapt to varying environmental temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…In Drosophila and Cephlopod species, reduced environmental temperatures leads to decreased body temperature and increased RNA editing (Garrett and Rosenthal 2012;Savva et al 2012;Buchumenski et al 2017;Yablonovitch et al 2017b). In flies, decreased temperatures result in increased editing at a recoding editing site in the ADAR mRNA itself, as well as increased editing at 55 additional protein coding (CDS) sites (Savva et al 2012;Buchumenski et al 2017). The absence of RNA editing results in perturbed acclimation to temperature changes, suggesting an adaptive function for temperature-sensitive RNA editing (Buchumenski et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In flies, decreased temperatures result in increased editing at a recoding editing site in the ADAR mRNA itself, as well as increased editing at 55 additional protein coding (CDS) sites (Savva et al 2012;Buchumenski et al 2017). The absence of RNA editing results in perturbed acclimation to temperature changes, suggesting an adaptive function for temperature-sensitive RNA editing (Buchumenski et al 2017). Similarly, octopus species that reside in colder temperatures have higher rates of RNA editing of potassium channels, which is an adaptation that alters Kv1 channel kinetics to improve function in the cold (Garrett and Rosenthal 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To date there is largely evidence against (Villanueva-Cañas et al 2014) but little evidence for (Matos-Cruz et al 2017) genetically encoded cold-adaptation of proteins that could support function at low temperature during hibernation. mRNA editing has the potential to cause adaptive changes in proteins that leave no signature in the genome; this mechanism is used for temperature adaptation of proteins in ectotherms (Garrett and Rosenthal 2012;Savva et al 2012;Buchumenski et al 2017) . Here we demonstrate for the first time rampant, temperature-dependent RNA editing during hibernation, with most sites falling outside of protein coding regions.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila and Cephlapod species, reduced environmental temperatures leads to decreased body temperature and increased RNA editing (Buchumenski et al 2017;Garrett and Rosenthal 2012;Savva et al 2012;Yablonovitch et al 2017b) . In flies, decreased temperatures result in increased editing at a recoding editing site in the ADAR mRNA itself, as well as increased editing at 55 additional protein coding (CDS) sites (Savva et al 2012;Buchumenski et al 2017) . The absence of RNA editing results in perturbed acclimation to temperature changes, suggesting an adaptive function for temperature-sensitive RNA editing (Buchumenski et al 2017) .…”
Section: Introductionmentioning
confidence: 99%